What is Hermeneutics? - Romualdo E. Abulad (Kritike: An Online Journal of Philosophy, 2007)
Hermeneutics is the art of interpretation - we shall not forget that and we will return to it again and again, for that is what hermeneutics is - the art of interpretation. We might do well, however, to stare at the word ‘hermeneutics' just by way of a starting point. Hermeneutics - the word goes back to a name, Hermes. Who is Hermes? Among the earliest references to him is made by no less than Plato in the dialogue, Cratylus.1 The dialogue begins rather abruptly, with someone called Hermogenes inviting Socrates to be a party to an argument between him (Hermogenes) and Cratylus. Cratylus is therefore one of the characters in the dialogue, and it is his name that is also given to the dialogue. The other party to it is Hermogenes, a name which literally means ‘son of Hermes'. Socrates suspects that Cratylus is making fun of Hermogenes, saying that the latter is "no true son of Hermes, because (he - Hermogenes - is) always looking after a fortune and never in luck."